Systemic Racism against Unaccompanied Child Immigrants in Tori et Lokita (2022) - Salsabila Fitri Suteja; Diah Kartini Lasman (Franconesia, 2026)
Tori et Lokita (2022), a Belgian-French film by Jean-Pierre Dardenne and Luc Dardenne, portrays the struggles of two child immigrants from Benin and Cameroon attempting to survive in Belgium. This study examines how the film represents systemic racism and racial discrimination embedded within institutional structures. Employing a descriptive qualitative method, the research analyzes narrative, cinematographic, character, setting, and dialogue elements. Narrative analysis is conducted using A.J. Greimas’ actantial model and functional structure, while Critical Race Theory by Richard Delgado and Jean Stefancic is used to identify forms of systemic racism. The findings reveal that systemic racism is represented through the main characters’ experiences, particularly in the ineffective implementation of asylum policies for unaccompanied minors, institutional distrust toward immigrants, and the exploitation of individuals based on race and legal status. This study highlights film not only as a representational medium but also as a critical lens that exposes systemic racism and structural inequalities through the lived experiences of unaccompanied minors.